Employee Perceptions of Competency Development Effectiveness in Multinational Companies: A Qualitative Insight - Megawati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the effectiveness of competency development programs in multinational companies and their influence on employee career development and performance. The research aims to identify key factors that enhance or hinder the success of such programs from the employees’ perspective. A qualitative approach was used, involving in-depth interviews and Focus Group Discussions (FGDs) with 20 employees who had participated in the programs. Data collection focused on employee experiences, perceived relevance of training, and managerial support. The findings indicate that training effectiveness is significantly influenced by three main factors: the alignment of training materials with daily work tasks, active managerial support, and the degree of personalization within the training content. Employees reported higher motivation and a stronger sense of career advancement when the training was directly applicable to their job roles. Managerial support also played a critical role in reinforcing learning outcomes and encouraging practical application in the workplace. The study concludes that to improve the impact of competency development programs, organizations should tailor training content to individual roles and ensure continuous engagement from leadership throughout the training process. These findings contribute to the understanding of effective talent development practices in global business environments.